PENDAMPINGAN USAHA DUPA GUNA MENINGKATKAN KEMAMPUAN PENGRAJIN - Ni Nyoman Sri Rahayu Damayanti; I Ketut Puja Wirya Sanjaya; I MAde Aditya Mantara Putra (Politeknik Negeri Sriwijaya, 2020)
Incense is one of the results of the physical culture of the traditions that exist in Bali. There are some limitations that felt by the incense craftsmen. They have no ability to make a simple financial statement. Partners do not understand about sales system other than cash sales. Another sales system is believed to be able to attract more consumers, so that the sales value will increase. Partners also do not have an understanding of how to make a sales agreement. There are several problem solutions that are offered to overcome these obstacles. First, counseling on making a simple financial report, second is counseling on consignment sales system, and the last is counseling on making consignment sales agreement. After all of the work program are implemented, now the partner can make a daily cash note which is consist of daily cash notes on hand and daily cash notes on bank account . In addition, partner also know about consignment sales system and they can make a sales agreement. The work program already to improve the abilities and the skills of the craftsmen